Composite Implicit Iteration Process for Asymptotically Hemi-Pseudocontractive Mappings (Journal of Mathematical Study, 2021)
In Banach space, the composite implicit iterative process for uniformly L-Lipschitzianasymptotically hemi-pesudocontractive mappings are studied, and thesufficient and necessary conditions of strong convergence for the composite implicititerative process are obtained.